(untitled) (PRÁXIS EM SAÚDE, 2025)
This study discusses the role of creative interventions in psychology applied to the oncological context, focusing on art therapy, music therapy, and therapeutic writing practices. The objective is to analyze how these techniques contribute to the psychological support of cancer patients, promoting alternative interventions that complement conventional treatments. The research used a bibliographic review methodology, examining relevant studies on the social, emotional, and physical benefits of these interventions. In this regard, the results revealed that they enhance patients’ resilience, improve their physical and mental health, and help them cope with the disease. In summary, it is emphasized that creative interventions are essential for the care of oncology patients, and the need for more scientific studies on this topic is highlighted in order to expand the technical repertoire of professionals.